ISRĀ'ĪLIYYĀT DISCOURSE IN ARCHIPELAGO INTERPRETATION: Bisri Mustafa's Study of The Tafsir Al-Ibriz - Lukman Nul Hakim; Iffatul Bayyinah; Eko Zulfikar; Kusnadi Kusnadi (AL-TAHRIR, 2023)
The use of Isrā’īliyyāt in interpretation is still questioned. However, Isrā’īliyyāt has colored several commentaries' works, including Tafsir Nusantara. One of which is Tafsir al-Ibriz. Using the Javanese language and Pegon writing as the interpreter's selected language and introduction writing is one of the interpretation's distinctive features. Historically, Isrā’īliyyāt is frequently found in bi al-ma'tsur interpretations. Still, it turns out that the dominating al-Ibriz Tafsir ra'yi is also found by Isrā’īliyyāt, which has its peculiarities in its application and relation to the sociocultural context of writing. This study employed library research using qualitative approaches. Tafsir al-Ibrz was the main data source. In contrast, the secondary sources included journals and others. Documentation strategies were used in the analytical methodology. It also used the content analysis method of Norman Fairclough's discourse analysis methodology. In this research, the Isrā’īliyyāt sample accounts for Ashhab al-Kahf, Prophet Noah's Ark, and Luqman's identity. According to the findings of this study, Al-Ibriz's Tafsir includes Isrā’īliyyāt and then comments on the advantages and suggestions that can be followed. Regarding its sociocultural context, Tafsir al-Ibriz was composed amid Javanese society's social culture, which is still saturated with the tradition of believing in ancestors and the love of stories. The narrative of Isrā’īliyyāt described in this study is a sociological strategy meant to lead individuals away from their ancestral/mystical beliefs and toward the Qur’an.